Application of fluorinated solvents for cesium ion extraction from aqueous solution by D2EHPA. Issue 18 (11th December 2020) - Tajima, Hideo; Ui, Hiroki; Minagawa, Mai; Suzuki, Motoshi; Kikuchi, Aoi; Nanba, Shou-ichi; Taguchi, Youji
ABSTRACT: This study focuses on the application of fluorinated solvents, HCFC-225 and HFE347pc-f, for cesium removal and volume reduction of cesium-containing solutions in solvent extraction. The fluorinated solvents extracted cesium ions very well with Bis(2-ethylhexyl) phosphoric acid (D2EHPA) in comparison with a conventional solvent, cyclohexane. The extraction mechanism corresponded to the well-known metal ion extraction process of D2EHPA. By optimizing the solution volume ratio of D2EHPA–containing fluorinated solvent to aqueous solution and performing multiple extractions, over 90% cesium removal was achieved. Because fluorinated solvents can be distilled easily, cesium removal and volume reduction of cesium-containing materials can be achieved simultaneously.